KIC 6761539, a fast rotating γ Dor – δ Sct hybrid star. Issue Volume 9:Issue S301(2013) (18th February 2014) - Herzberg, W.; Corre, D.; Uytterhoeven, K.; Roth, M.
Abstract: KIC 6761539 is one of many fast rotating γ Doradus – δ Scuti hybrid pulsators. A search for possible regularities in the frequency spectrum is performed and a first stellar model is presented.